Possibilities of the self-sampling method application in the cervical cancer screening (review) - I A Apolikhina; L K Bashirova; E A Gorbunova (IP Berlin A.V., 2018)
It was performed an analysis of literature data on the possibility of using self-sampling methods for the screening of cervical cancer. It is indicated that the slow progression of the disease, the presence of several stages of precancerous conditions and the relative accessibility of the tumor for manipulation provide opportunities for timely diagnosis and prevention of the tumor. It is reported that a number of specialists believe that an independent sampling of material for human papillomavirus analysis can be considered as an alternative method for screening cervical cancer. Using this approach will significantly increase the coverage of the population participating in screening programs. The need for further research on improving the technical aspects and assessing the clinical and economic characteristics of the application of the method of self-sampling of cervical-vaginal material to be separated in clinical and epidemiological practice was noted.